A plea for an early ultrasound-clinical integrated approach in patients with acute heart failure. A proactive comment on the ESC Guidelines on Heart Failure 2016. (15th October 2017) - Tavazzi, G.; Neskovic, A.N.; Hussain, A.; Volpicelli, G.; Via, G.
Abstract: Background: The European Association of Cardiology (ESC) Guidelines on the diagnosis and treatment of acute heart failure (AHF) indicate prompt therapy initiation and performance of relevant investigations as paramount. Specifically, echocardiography prior to treatment is advocated only with hemodynamic instability, and the evaluation of clinical signs of peripheral perfusion and congestion is suggested as guidance for early interventions. Given the growing body of evidence on the diagnostic/monitoring capabilities of bedside ultrasound (including focused cardiac ultrasound, comprehensive echocardiography, lung ultrasound), we discuss the potential benefit of an integrated clinical/ultrasound approach at the very early stages of acute heart failure. Methods and Results: We proposed a narrative review of the current evidence on the clinical-ultrasound integrated approach to AHF, with special emphasis on the components of the early diagnostic-therapeutic workup where cardiac, inferior vena cava and lung ultrasound showed high diagnostic accuracy and the capability of substantially changing an exclusively clinically-oriented patient management. A proactive comment to the ESC guidelines is made, suggesting an integration of clinical and biochemical assessment, as defined by guidelines, with combined bedside ultrasound on may help in the definition of AHF pathophysiology and treatment. Conclusion: A multi-organ integrated clinical-ultrasound approach should be advocated as part of the clinical-diagnostic workup at AHF very early phase. Whenever competence and technology available, bedside ultrasound, along with clinical and biochemical assessment, should target AHF profiling, identify the cause of AHF, and subsequently aid disease course and response to treatment monitoring. Highlights: Diagnosis of acute heart failure relies on clinical and biochemical examination. Echocardiography is not routinely recommended at the acute heart failure onset. Echo and lung ultrasound are more accurate than clinical exam in AHF diagnosis. Clinical and ultrasound integration upturns the accuracy of AHF phenotype definition. Precise AHF phenotype identification may allow a better tailored therapy.